2018
DOI: 10.18203/2349-2902.isj20181136
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to assess clinical profile and golden period for operative intervention in patients with perforation peritonitis

Abstract: Background: Perforation peritonitis constitutes one of the most common surgical emergencies encountered by surgeons. Even with modern treatment, diffuse peritonitis carries a high morbidity and mortality rate.Methods: The prospective study was conducted at department of surgery on 50 patients of perforation peritonitis admitted in emergency department of hospital. Detailed history, clinical examination and investigations were carried out. Patients were operated upon and findings were noted. Comparisons were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…This observation is consistent with results of available literature which showed that most of the series from India have reported male preponderance in secondary peritonitis [7][8][9][10]. Malik et al showed a ratio of male to female to be 5.25:1 [12]. Yadav et al [13] in their study at Delhi reported a male to female ratio of 4.9:1.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This observation is consistent with results of available literature which showed that most of the series from India have reported male preponderance in secondary peritonitis [7][8][9][10]. Malik et al showed a ratio of male to female to be 5.25:1 [12]. Yadav et al [13] in their study at Delhi reported a male to female ratio of 4.9:1.…”
Section: Discussionsupporting
confidence: 89%
“…Yadav et al [13] and Mabewa et al [27] reported wound dehiscence in 3.9 and 11.34% of patients, while surgical site infection rates were 19.5 and 18.6%, respectively. In another study by Malik et al [12], 42% of their patients developed postoperative complications with wound infection in 38% of patients, pneumonia in 24%, and burst abdomen in 12% of patients. In our study we observed that the complication rate was higher in patients with enteric perforation which was 33.33% followed by peptic ulcer disease in 19.49% of cases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a research by Ranju Singh et al among 84 patients 100% who died had symptoms more than 3 days [26]. Timing of presentation over 24 hours was found to be a signi cant factor in developing of post-operative mortality and morbidity [25].…”
Section: 22% -----------mentioning
confidence: 99%